1998
DOI: 10.1046/j.1523-5378.1998.08038.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐Up of Helicobacter pylori Positive Gastritis and Argyrophil Cells Pattern During the Natural Course of Gastric Ulcer

Abstract: This study demonstrates that ACH evolves during the natural course of GU, alongside the development of chronic atrophic gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Another 4 articles were excluded for the following reasons: all patients had either chronic gastritis or CAG at baseline, incidence of CAG was based on biopsies and not on study participants, incidence of CAG and metaplasia or either of them were grouped together and in one study, no mean follow-up time could be estimated. Due to these exclusions, only 14 studies (from 15 articles) with information on the incidence of CAG could be included in this review [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. According to the above described criteria, all of these studies included more than 15 study participants who were diagnosed to be free of CAG at baseline, either by histology ('normal' or 'superficial gastritis') or by serum pepsinogen (PG) levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 4 articles were excluded for the following reasons: all patients had either chronic gastritis or CAG at baseline, incidence of CAG was based on biopsies and not on study participants, incidence of CAG and metaplasia or either of them were grouped together and in one study, no mean follow-up time could be estimated. Due to these exclusions, only 14 studies (from 15 articles) with information on the incidence of CAG could be included in this review [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. According to the above described criteria, all of these studies included more than 15 study participants who were diagnosed to be free of CAG at baseline, either by histology ('normal' or 'superficial gastritis') or by serum pepsinogen (PG) levels.…”
Section: Resultsmentioning
confidence: 99%
“…2 of the studies were conducted in multiple centres in different countries [20,22]. Studies were carried out in Sweden, [10] Columbia, [11] the Netherlands, [12,13] the Netherlands and Sweden, [14] Finland, [15] Estonia, [16,24] Japan, [17,23] USA, [18] Slovenia, [19] Australia, Canada, Germany, and the Netherlands, [20] Germany [21] and Denmark, Finland, Norway and Sweden [22]. Most of the studies were not population-based and consisted of symptomatic patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, they mostly included selected study populations, the majority of which consisted of patients with a variety of gastric disorders. [7][8][9][10][11][12][13][14] In the population-based gastroscopy studies by Correa et al 15 and Vorobjova et al 16 conducted in high risk populations of Columbia and Estonia, incidence of CAG was reported to be 7.1% per year (in the gastric corpus and antrum simultaneously) and 1.9% per year (in the gastric corpus), respectively. In two other population-based studies from Japan, 17,18 in which different pepsinogen-based definitions were used to define CAG, annual CAG incidences were reported to be 2.7% and 1.3%, respectively.…”
mentioning
confidence: 98%
“…The few existing longitudinal studies reported incidences ranging from 0 to 11% per year. However, they mostly included selected study populations, the majority of which consisted of patients with a variety of gastric disorders 7–14. In the population‐based gastroscopy studies by Correa et al15 and Vorobjova et al16 conducted in high risk populations of Columbia and Estonia, incidence of CAG was reported to be 7.1% per year (in the gastric corpus and antrum simultaneously) and 1.9% per year (in the gastric corpus), respectively.…”
mentioning
confidence: 99%
“…In their follow-up study of gastric ulcer patients, Maaroos and colleagues [1] document the development of argyrophil-cell hyperplasia (ACH) in corpus mucosa in 45% of cases. The degree of ACH ran parallel to the progression of corpus atrophic gastritis.…”
mentioning
confidence: 99%